Increasing Accuracy of In Vitro Cancer Models: Engineering Stromal Complexity into Tumor Organoid Platforms. Issue 12 (11th August 2021) - Chakraborty, Srija; DePalma, Thomas J.; Skardal, Aleksander
Abstract : Cancer is a life‐threatening disease, and even upon successful treatment, recurrence often occurs. A wide variety of preclinical models exist to effectively study cancer and design more efficient treatments. However, a majority of cancer models cannot accurately recapitulate cancer as it exists in humans. Animal models physiologically differ from humans. In vitro models, such as organoids, allow construction with human‐based components, but most fail to accurately mimic the overall tumor microenvironment (TME), which is composed of stromal and immune cells, as well as a complex extracellular matrix (ECM). However, more recent versions of these in vitro tumor models are increasingly complex and include both engineered ECM and the bidirectional, biomolecular crosstalk between different stromal cell components, particularly fibroblasts which are key players in the TME. Therefore, studying these components gives a more detailed insight into how tumors develop, interface with surrounding stromal and tissue architecture, and respond to therapies. Herein, a range of in vitro tumor model form factors is described, and the role of fibroblasts and ECM in cancer is also discussed, with a focus on how their inclusion in bioengineered in vitro and ex vivo tumor models better recapitulate the physiological complexities of cancer. Abstract : Thus far, the majority of in vitro cancer models have failed to recapitulate the complexity of tumors and their nontumorigeneic components, such as stroma in the form of cells and extracellular matrix (ECM). Herein, a variety of in vitro tumor model form factors and how inclusion of fibroblasts and ECM stromal components can improve their accuracy and effectiveness are described.